High prevalence of mental disorders: a population-based cross-sectional study in the city of Ilam, Iran - Kakaei, Hojatollah; Maleki, Farajolah; Biderafsh, Azam; Valizadeh, Reza; Mansournia, Mohammad Ali; Pakzad, Iraj; Pakzad, Reza (Frontiers in Psychiatry, 2023)
Aim: To determining the age-sex standardized prevalence and risk factors of depression symptoms, anxiety symptoms and stress symptoms in Ilam city Method: In this population-based cross sectional study, 1350 people were invited by multi stage stratified cluster random sampling method. Depression, anxiety and stress symptoms were measured by the DASS-21 standard questionnaire. For data analysis, multiple ordinal logistic regression was used in Stata version 12 software. A significance level of 5% was considered. Results: The data of 1431 people was analyzed. The age-sex standardized prevalence (95% CI) of severe depression symptoms, anxiety symptoms and stress symptoms was 19.90% (17.64 to 22.16), 25.95% (23.48 to 28.43) and 15.75% (13.69 to 17.81), respectively. There were a positive association among depression symptoms with female gender (OR: 1.52; p: 0.003), Kurd race (OR: 2.15; p: 0.004), low educational level (OR: 1.37; p: 0.031), job losing history (OR: 1.64; p: 0.001), mental disorders history (OR: 2.17; p< 0.001), hopelessness to future (OR: 5.38; p<0.001) and history of other diseases (OR: 1.67; p<0.001). There was a positive association among anxiety symptoms with female gender (OR: 1.72; p<0.001), job losing history (OR: 1.53; p: 0.003), mental disorders history (OR: 2.11; p< 0.001), hopelessness to future (OR: 3.33; p<0.001) and history of other diseases (OR: 1.97; p<0.001). Hopelessness to future and history of other diseases were the most effective variables on anxiety symptoms and stress symptoms. Conclusion: A significant proportion of Ilam's urban population suffers from mental disorders. Increasing people's awareness, counseling centers and improving infrastructure should be noticed for mental health policymakers who work in the province.